The Use Of A Metabolic Disorder Index As A Predictor For Metabolic Eliminations In Endurance Horses - Lawan Adamu; Ahmad Fadly Nurullah b.Rasedee; Noraniza Mohd Adzahan; Abdullah Rasedee; Bashir Ahmad (W.B. Saunders Ltd, 2024)
Indexed by SCOPUS